The refurbishment of Telford's Nantwich Aqueduct, UK. Issue 1 (16th September 2019) - Hunt, Gavin; Day, William
Abstract : The Grade II*-listed Nantwich Aqueduct (Cheshire, UK) was designed by Thomas Telford and completed in 1828. It carries the Shropshire Union Canal across the A534 Chester Road, so forming the striking 'Gateway to Nantwich'. Ironwork was provided by Telford's long-time collaborator and recognised master of his art, William Hazledine. Despite its modest scale relative to the previous great and iconic structures that the pair had previously been responsible for, Nantwich Aqueduct showcases Telford's and Hazledine's respective expertise at the swansong of their careers. The aqueduct underwent refurbishment works in September 2015. Works which were found to be required included repairs to several original cast-iron features, including a replacement arch spandrel plate, along with restorative work to various stone and brickwork elements. Due to the aqueduct's heritage, close consultation with the heritage authority was duly undertaken from the outset. Measures were taken to satisfy the stringent requirements, such as in situ and laboratory metallurgy testing, masonry matching and early involvement with specialist structural cast-ironwork contractors.